2018
DOI: 10.1177/0963689717725755
|View full text |Cite
|
Sign up to set email alerts
|

Fighting against Skin Aging

Abstract: As the most voluminous organ of the body that is exposed to the outer environment, the skin suffers from both intrinsic and extrinsic aging factors. Skin aging is characterized by features such as wrinkling, loss of elasticity, laxity, and rough-textured appearance. This aging process is accompanied with phenotypic changes in cutaneous cells as well as structural and functional changes in extracellular matrix components such as collagens and elastin. In this review, we summarize these changes in skin aging, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
269
0
28

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 519 publications
(297 citation statements)
references
References 103 publications
(121 reference statements)
0
269
0
28
Order By: Relevance
“…Furthermore, many studies showed that skin aging and skin wrinkling may be reduced by the action of the antioxidant activity of various botanical extracts [58,59]. Aumeeruddy-Elalfi et al [22] showed that the inhibitory potential of essential oils extracted from some medicinal plants make them potential candidates for the cosmetic (skin aging) and pharmaceutical industries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many studies showed that skin aging and skin wrinkling may be reduced by the action of the antioxidant activity of various botanical extracts [58,59]. Aumeeruddy-Elalfi et al [22] showed that the inhibitory potential of essential oils extracted from some medicinal plants make them potential candidates for the cosmetic (skin aging) and pharmaceutical industries.…”
Section: Discussionmentioning
confidence: 99%
“…Skin aging, a complex biological process that can be modulated by several intrinsic (chronological or intrinsic skin aging) and environmental factors (e.g., UV radiation, extrinsic skin aging), is accompanied by both phenotypic changes in cutaneous cells and structural and functional changes of extracellular matrix (ECM) components, namely collagens, elastin and proteoglycans that are needed to maintain the tensile strength, elasticity and hydration of the skin [4,5]. Mitochondrial DNA damage, increased reactive oxygen species (ROS) production, and telomere shortening are considered to be major players during intrinsic skin aging [4,5]. Moreover, the accumulation of replicative old senescent skin cells may also promote the pathological remodeling of ECM [4].…”
Section: Introductionmentioning
confidence: 99%
“…31 Aging, due to both intrinsic and extrinsic factors, affects the overall ability of the skin to retain moisture and produce its own hyaluronic acid. 32 Evidence suggests that hyaluronic acid delivery through injections and formulations is a valuable solution for retaining moisture within the skin. 33 Several analyses were performed on the formulated emulsion to demonstrate applicability.…”
Section: Introductionmentioning
confidence: 99%